Indirect taxation (printed at the Office of the "Standard of Freedom", 1849)
Contains section XXIV(2nd part)-XXVIII(1st part), continued from tract no. 21, to be continued in tract no. 224. - Issued by the Liverpool Financial Reform Association. - In pamphlet volume with covertitle : Tracts of the Liverpool Financial Reform Association.